ANALYSIS OF THE INFLUENCE OF COMPANY SIZE, AUDIT COMMITTEE, AND AUDITOR OPINION ON AUDIT DELAY IN FOOD AND BEVERAGE MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Riduwan Riduwan (Income, 2026)
This study aims to analyze the influence of Company Size (X1), Audit Committee (X2), and Auditor Opinion (X3) on Audit Delay (Y) in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2015-2017. This study uses a purposive sampling method of 12 companies with 3 years of observation. The data in this study are secondary and documentation with two quantitative and qualitative approaches. The method used is the method of multiple linear regression analysis and hypothesis testing. The results showed a partial test .The size of the company had no effect on Audit delay, The audit committee has no effect on audit delay and The auditor's opinion affects the audit delay. In a simultaneous test of company size, audit committee and auditor opinion affect the audit delay. The independent variable in this study had an effect of 30.8% and the rest was influenced by other variables not examined in this study.